SULPHUR ISOTOPE CHARACTERISTICS OF METAMORPHOSED CU-(ZN) VOLCANOGENIC MASSIVE SULPHIDE DEPOSITS IN THE NORWEGIAN CALEDONIDES - Cook N.J.; Hoefs J. (My University, 1997)
Sulphur isotope data are presented for 86 separated samples of pyrite and other sulphides and four anhydrites from within five massive sulphide deposits in the Norwegian Caledonides, each of which was metamorphosed at different facies conditions during the Caledonian Orogen. Although the isotopic compositions fall within a relatively limited range (δ34S ranging from -8 to +12%%, with most samples clustered between -2 and +9%%), each deposit is isotopically distinct. Variations between average δ34S values for the various deposits, and between sub-groups identified in the data for the Sulitjelma, Gjersvik and Lokken deposits are best explained by differences in Eh, pH and other physico-chemical conditions during syngenetic formation and/or mildly differing sources of sulphur. Regional metamorphism did not lead to an extensive degree of homogenisation, and it is proposed that primary patterns have been largely preserved. Lithostratigraphic control of isotope compositions is evident and relative enrichment in 34S in disseminated (distal) and stockwork (feeder zone) ore facies is a feature of several deposits. Although the metamorphic episode was effectively a closed system as far as S isotopes are concerned, the structurally-controlled mobilisation of sulphides in some parts of massive sulphide lenses at Sulitjelma has apparently led to some considerable modification of S-isotope signatures, typified by pyrites with δ34S values of -8 to -4%%. However, this would appear to have taken place on a highly localised basis. The data shed new light on the origin of the abundant anhydrite at Sulitjelma, strongly suggesting that this mineral formed by oxidation of pre-existing sulphides subsequent to syngenetic deposition.
Keywords: SULPHIDES; SULPHUR ISOTOPES; CALEDONIDES; NORWAY; PYRITE; METAMORPHISM; SULITJELMA